Dwiguna Life Insurance Zilmer Reserves With The Cox-Ingersoll-Ross (CIR) Interest Rate - Hasriati Hasriati; Sukono Sukono; Ihda Hasbiyati; T.P Nababan; Aulia Kirana (Ilmu Komputer, FMIPA, Universitas Pakuan, 2023)
This article discusses Zilmer's reserve of dual purpose life insurance. Zillmer reserve is one type of modified premium reserve that is calculated using prospective reserves and Zillmer level of , which is the difference from gross premium and net premium in the 1st policy year is greater than standard loading, so it is necessary to find a way for the loading to be smaller than standard loading. Furthermore, in determining Zilmer's reserves using cox-ingersoll-ross interest rate (CIR) which will be expressed in the form of discount vaktor by estimating two parameters through variance.Â